Antioxidant, antihyperglycemic, and antihyperlipidemic properties of Chimonanthus salicifolius S. Y. Hu leaves in experimental animals: modulation of thioredoxin and glutathione systems, renal water reabsorption, and gut microbiota - Dong, Ruixia; Pan, Junjie; Zhao, Guangshan; Zhao, Qiuyan; Wang, Shiqiong; Li, Ning; Song, Lianjun; Huang, Xianqing; Miao, Shuxing; Ying, Junhui; Wu, Fangying; Wang, Dongxu; et al. (Frontiers in Nutrition, 2023)
Excessive calorie intake and physical inactivity have dramatically increased nutrient overload-associated disease, becoming a global public health issue. Chimonanthus salicifolius S. Y. Hu (CHI) is a homology plant of food and medicine in China and shows several health benefits. This work investigated the antioxidant activity, the alleviating effects, and the mechanism of action on diabetes and hyperlipidemia of CHI leaves. Results showed that CHI leaves infusion displayed in vitro antioxidant activity measured by ABTS and ferric reducing antioxidant power methods. In wild-type Kunming mice, CHI leaves infusion consumption activated the hepatic antioxidant enzymes, including glutathione reductase, glutathione S-transferase, glutathione peroxidase and thioredoxin reductase as well as thioredoxin reductase 1. In alloxan-induced type 1 diabetic mice, CHI leaves infusion ameliorated diabetic symptoms, including polyuria, polydipsia, polyphagia and hyperglycemia, in a dose-dependent and time-course manners. The mechanism involved CHI leaves up-regulating renal water reabsorption associated protein – urine transporter A1 – and promoting the trafficking of urine transporter A1 and aquaporin 2 to the apical plasma membrane. Despite this, in high-fat diet-induced hyperlipidemic golden hamsters, CHI leaves powder did not significantly affect on hyperlipidemia and body weight gain. This might be attributed to CHI leaves powder increasing the calorie intake. Interestingly, we found that CHI leaves extract containing a lower dose of total flavonoid than CHI leaves powder pronouncedly reduced the levels of total cholesterol, triglyceride, and low-density lipoprotein cholesterol in serum in golden hamsters fed a high-fat diet. Furthermore, CHI leaves extract elevated the diversity of gut microbiota and the abundance of Bifidobacterium and Ruminococcaceae_UCG-014. It also decreased the abundance of Lactobacillus at the genus level in golden hamsters fed a high-fat diet. Overall, CHI leaves benefit oxidative stress prevention and metabolic syndrome amelioration in vivo.